The role of obesity, sleep apnea, and elevated intracranial pressure in spontaneous cerebrospinal fluid leaks. Issue 5 (October 2019) - Rabbani, Cyrus C.; Saltagi, Mohamad Z.; Nelson, Rick F.
Abstract : Purpose of review: Spontaneous cerebrospinal fluid (sCSF) leaks often occurs in middle age, obese females. Here we investigate the role of obesity, idiopathic intracranial hypertension (IIH), and obstructive sleep apnea (OSA) in the pathophysiology of sCSF leaks. Recent findings: The association of obesity and sCSF leaks has been well established in many studies. It has now been revealed that sCSF leak patients have thinner calvariums along with the skull base. An intracranial process likely leads to calvarium and skull base thinning in sCSF leaks patients since this occurs independent of extracranial bone thinning and independent of obesity. OSA, which is known to cause spikes in intracranial pressure (ICP), has been found to be significantly prevalent in the sCSF population and has been shown to lead to both calvarial and skull base thinning. Chronically elevated ICP (IIH) has also been shown to impact calvarial and skull base thicknesses. Summary: The incidence of sCSF leaks has increased in recent decades along with an increasing rate of obesity. OSA and IIH, which are obesity-related factors and cause transient and chronic elevations in ICP, have now been implicated as critical factors leading to calvarial and skull base thinning and resultant sCSF leaks.